Ions in superfluid helium: measurement of the roton limited mobility - Gunther, H.; Foerste, M.; Putlitz, G. zu; Schumacher, Th. (Физика низких температур, 1996)
Different ions are used as microscopic probes for superfluid helium at temperatures ranging from 1.3 to 2.2 K. The ionic mobilities may provide new insight into the so far not well understood microscopic ion-roton scattering process. An ion source, which allows implantation of a great variety of impurity ions into liquid helium, is presented. Low-field velocities of Na⁺, Ag⁺ and Au⁺ ions are reported as a function of the electrical drift field and the temperature. Moreover, a temporal series of images taken by an intensifying CCD camera is presented, showing a cloud of moving Ba⁺ ions.